Principles of leadership - Dubrin, Andrew J. (South-Western Cengage Learning, 2013)
Perfect for instructors who take a practical, skill-building approach to teaching leadership, PRINCIPLES OF LEADERSHIP, 7E, International Edition provides an ideal balance of essential theory and real-world applications. Andrew DuBrin, a highly respected author and consultant, incorporates the latest research on leadership and current business practices from academic journals and popular periodicals. The text provides students with a strong practical foundation by introducing leaders they can relate to and reinforcing their knowledge with frequent skill-building activities. Key updates include new opening vignettes and end-of-chapter cases, numerous additional skill-building exercises, and video discussion questions at the end of each chapter. An all-new CourseMate interactive study tool site features additional video content, premium quizzing, and links to both the Career Transitions job search tool and Cengage's KnowNOW blog, which is constantly updated and provides an intuitive view of current events.